2013
DOI: 10.4137/bbi.s10501
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Insilico Analysis of Retinoblastoma Serum microRNA Profile and Gene Targets towards Prediction of Novel Serum Biomarkers

Abstract: Retinoblastoma (RB) is a malignant tumor of the retina seen in children, and potential non invasive biomarkers are in need for rapid diagnosis and for prognosticating the therapy. This study was undertaken to identify the differentially expressed miRNAs in the serum of children with RB in comparison with the normal age matched serum, to analyze its concurrence with the existing RB tumor miRNA profile, to identify its novel gene targets specific to RB, and to study the expression of a few of the identified onco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 45 publications
(87 reference statements)
2
48
0
Order By: Relevance
“…In recent years, this kind of combination analysis of any identified miRNA, its corresponding target genes, enriched KEGG pathways, and even miRNAmRNA network were performed in cancer studies (Satoh, 2012;Liu et al, 2014), particularly in cancer biomarker discoveries (Romero-Cordoba et al, 2012;Beta et al, 2013). In this study, based on miRWalk database combined with DAVID 6.7 tool and mirfocus 3.0, bioinformatics prediction and Enriched KEGG pathways analysis of miR-196a-5p indicated that both predicted target genes and validated target genes of miR-196a were clustered in cancer associated KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, this kind of combination analysis of any identified miRNA, its corresponding target genes, enriched KEGG pathways, and even miRNAmRNA network were performed in cancer studies (Satoh, 2012;Liu et al, 2014), particularly in cancer biomarker discoveries (Romero-Cordoba et al, 2012;Beta et al, 2013). In this study, based on miRWalk database combined with DAVID 6.7 tool and mirfocus 3.0, bioinformatics prediction and Enriched KEGG pathways analysis of miR-196a-5p indicated that both predicted target genes and validated target genes of miR-196a were clustered in cancer associated KEGG pathways.…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, it was estimated that there were 2,580 new cases in the United States (3). Various factors are involved in the carcinogenesis and development of retinoblastoma, including genetic and epigenetic alterations to oncogenes and tumor suppressor genes, and a large number of these have previously been demonstrated to regulate cell growth, the cell cycle and apoptosis (4,5). In developed countries, >95% of patients with retinoblastoma have a good prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…While each tumor type is characterized by its own unique miRNA profile, it is interesting to note that several miRNAs appear to be up-or down-regulated in almost all tumor samples relative to normal adjacent tissue. Beta et al [15] studied the miRNA profile of RB sample using in silico methods and found that 21 miRNAs are upregulated and 24 are down regulated in RB.…”
Section: Discussionmentioning
confidence: 99%